Weight martingale-ergodic and ergodic-martingale theorems - Ganiev, Inomjon; Othman, Raihan (IDOSI Publications, 2013)
In this paper we prove weighted martingale-ergodic and weighted ergodic-martingale theorems. Furthermore, analogous dominant and maximal inequalities for weighted martingale ergodic sequences and weighted ergodic martingale averages are also obtained.